Characterization of Malaria S antigen Protein Interaction with Human Erythrocytes - Nair, Sanjana. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Athar Chishti.; Keyword: Pharmacology.